Methanogenesis kinetics of organic matter of the leachate in an up-flow anaerobic sludge blanket reactor - Mohamad Ali Fulazzaky; Ali Yuzir; Tiffany Messer; Agus Sofyan (Waste Management Bulletin)
Understanding the treatment of leachate mediated by the development of anaerobic sludge makes it possible to create an effective design process of biodegradation technology. This study used an up-flow anaerobic sludge blanket (UASB) reactor equipped with a gas–liquid-solid separator to capture CH4 for treating landfill leachate to improve understanding of methanogenesis kinetics of organic matter. The performance of UASB was able to remove 154.75 g/L of chemical oxygen demand (COD) content of the leachate originally anticipated to emit 2.99 L of CH4 production into the atmosphere. The trend in the variation of internal mass transfer (IMT) factor was close to the global mass transfer factor; however, it was far higher than that of external mass transfer (EMT) factor. After 30 days of the experiment, methanogenesis kinetics of organic matter of the leachate were supported mainly by the breakdown of complex molecules. The rate-limiting step of CH4 desorption was controlled by IMT at the beginning and then by EMT after 30 days of the experiment. The strongly decreased EMT factor was counterbalanced by an increased value of the IMT factor at before 5 days of the experiment. It would be of interest to predict the methanogenesis kinetics of CH4 desorption using the Generalized Fulazzaky equations, which cannot be evaluated using other models. Analysis of the methanogenesis kinetics of organic matter of the leachate provides a new insight into the performance of UASB reactor, which may contribute to advanced treatment of landfill leachate in the future.